Optimization of RNA Extraction from Aedes aegypti and Aedes albopictus - Saiku Rokhim; Ninik Fadhillah; Radinal Kautsar; Humayra Qurrata Aini; Yuanita Rachmawati (Biotropic : The Journal of Tropical Biology, 2023)
RNA extraction is the critical initial stage in analyzing certain gene expressions, further analysis using Real Time PCR technology, and performing virus detection. However, the process of extracting RNA is often hampered by the risk of contamination, resulting in low concentrations of RNA and low purity of RNA. This is often an obstacle in extracting mosquito RNA especially detecting Dengue Virus (Den-V). Dengue virus (Den-V) can cause dangerous diseases in humans such as Dengue Fever (DHF) which is transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. This study aims to find out the effective steps for extracting RNA from Aedes aegypti and Aedes albopictus mosquitoes. The method being compared is a commercial RNA extraction kit with modification (addition of β-mercaptoethanol) and without modification. The results showed that the best DNA concentration and purity were obtained in mosquito samples from modified process. The purity ratio of RNA extracted without modification was 1.971 (0.021 ± 0.800) while with modification it was 2.003 (0.011 ± 0.112). Aedes aegypti had a better average concentration of 7.146 µg/ml for unmodified RNA and 7.613 µg/ml for modified RNA. This research is expected to be a reference for further studies on viruses in Aedes aegypti and Aedes albopictus.